2019
DOI: 10.1007/s40262-019-00855-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Upadacitinib: Review of Data Relevant to the Rheumatoid Arthritis Indication

Abstract: Upadacitinib is a Janus kinase 1 inhibitor developed for treatment of moderate to severe rheumatoid arthritis (RA) and was recently approved by the US Food and Drug Administration for this indication in adults who have had an inadequate response or intolerance to methotrexate. Upadacitinib is currently under regulatory review by other agencies around the world. Ongoing trials are investigating the use of upadacitinib in other inflammatory autoimmune diseases. In this article, we review the clinical pharmacokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 30 publications
(82 reference statements)
1
42
0
4
Order By: Relevance
“…None of the covariates assessed (body weight, sex, race, ethnicity, age, renal/hepatic impairment) in the population pharmacokinetic analysis based on phase I–III clinical trials had a clinically relevant effect on upadacitinib exposure [ 71 , 72 ]. Therefore, the pharmacokinetics of upadacitinib are not expected to have a clinically meaningful effect on the efficacy or safety of upadacitinib.…”
Section: Benefit–risk Evaluationmentioning
confidence: 99%
“…None of the covariates assessed (body weight, sex, race, ethnicity, age, renal/hepatic impairment) in the population pharmacokinetic analysis based on phase I–III clinical trials had a clinically relevant effect on upadacitinib exposure [ 71 , 72 ]. Therefore, the pharmacokinetics of upadacitinib are not expected to have a clinically meaningful effect on the efficacy or safety of upadacitinib.…”
Section: Benefit–risk Evaluationmentioning
confidence: 99%
“…Administration of upadacitinib with the strong CYP3A inhibitor ketoconazole increased upadacitinib C max and AUC by 70% and 75%, respectively, whereas the administration of multiple doses of rifampin (a broad CYP inducer) decreased upadacitinib C max and AUC by approximately 50% and 60%, respectively 13 . Upadacitinib did not inhibit or induce the activity of CYP enzymes (CYP1A2, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, and CYP3A4) at clinically relevant concentrations, but in vitro studies demonstrated an increase in CYP2B6 mRNA expression at concentrations higher than those that are clinically relevant 14,15 . In a healthy volunteers study, chronic dosing of upadacitinib 30 mg once daily (a dose that is twice the recommended dose in RA) showed a limited effect on CYP3A activity (26% decrease in exposures of midazolam, a sensitive CYP3A substrate) and no relevant effects on CYP1A2, CYP2C9, CYP2C19, or CYP2D6 activity 16 .…”
mentioning
confidence: 90%
“…13 Upadacitinib did not inhibit or induce the activity of CYP enzymes (CYP1A2, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, and CYP3A4) at clinically relevant concentrations, but in vitro studies demonstrated an increase in CYP2B6 mRNA expression at concentrations higher than those that are clinically relevant. 14,15 In a healthy volunteers study, chronic dosing of upadacitinib 30 mg once daily (a dose that is twice the recommended dose in RA) showed a limited effect on CYP3A activity (26% decrease in exposures of midazolam, a sensitive CYP3A substrate) and no relevant effects on CYP1A2, CYP2C9, CYP2C19, or CYP2D6 activity. 16 A follow-up drug interaction study demonstrated no impact of upadacitinib on exposure of levonorgestrel and ethinylestradiol, 2 oral contraceptives that are substrates of CYP3A, confirming a lack of clinical relevance of the observed small effect of upadacitinib on midazolam exposure.…”
mentioning
confidence: 99%
“…Additionally, upadacitinib is currently under development for the treatment of several autoimmune diseases including ulcerative colitis [UC 12 ], Crohn's disease [CD [13][14][15] ], psoriatic arthritis 16,17 , giant cell arteritis 18 , axial spondyloarthritis 19 , and AD 20 . Upadacitinib pharmacokinetics were characterized following the administration of single and multiple doses of the immediate-release and extended-release formulations [21][22][23][24][25][26] . Upadacitinib plasma exposures were approximately dose proportional over the evaluated dose range across clinical studies and displayed no significant accumulation with repeated twice-daily dosing using the immediaterelease formulation or with QD dosing using the extended-release formulation 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Upadacitinib pharmacokinetics were characterized following the administration of single and multiple doses of the immediate-release and extended-release formulations [21][22][23][24][25][26] . Upadacitinib plasma exposures were approximately dose proportional over the evaluated dose range across clinical studies and displayed no significant accumulation with repeated twice-daily dosing using the immediaterelease formulation or with QD dosing using the extended-release formulation 21,22 . The extendedrelease tablet formulation of upadacitinib was developed to enhance patient compliance and has 76% oral bioavailability relative to the same dose of the immediate-release formulation 23 .…”
Section: Introductionmentioning
confidence: 99%